Obresti in plodovi pri neupravičeni obogatitvi - Možina, Damjan (Pravni letopis, 2019)
An internet domain name helps us identify any website and access it. Due to its distinguishing function, a recognisable internet domain has considerable economic significance as it increases website traffic. Therefore, domain name holder's debtors may want to cash in the property value of the domain to ensure payment of their claims against the creditor. However, the method of execution upon domain names is not clearly regulated in legislation. The article presents the basic technical characteristics of internet domain names and their registration; on this basis, it further examines the legal nature and legal protection of domain names. The author concludes that a domain name in itself should not be treated as an exclusive right. Nevertheless, execution upon a domain name can still be carried out by appraisal and sale of the complete set of domain name holder's contractual rights arising from its relationship with the domain name registry.
Keywords: obligacijsko pravo